HOMOSEXUALITY AND HOMOPHOBIA: CONCEPTS OR PREJUDICES? - Adaid, Felipe (2014)
This article aims to analyze, in an introductory way the concept of homosexuality under a critical focus, especially with regard to the issue of homophobia in order to transcend discussions that orbit the psychology and sociology. This time, since it is assumed that any attempt to understand categorization of sexuality points to a vision not only reductionist, but also biased. The question, then, marks the research can be formulated as follows: how can thinking homosexuality, taking into account the issue of homophobia in order to not fall into a discourse that reduces its complexity? Regarding the research method, the article will be carried out through literature review, through psychology and sociology texts. In this sense, the theoretical framework points to a structuralist nature.